KEANEKARAGAMAN JENIS SEMUT (formicidae) DI KAWASAN HUTAN GUNUNG SELINDUNG DESA TWI MENTIBAR KECAMATAN SELAKAU KABUPATEN SAMBAS - Rizal, Rizal; Rifanjani, Slamet; Kartikawati, Siti Masitoh (Universitas Tanjungpura, 2020)
Ants is a one of the biotic components in the forests of Kalimantan, this animal Â has a number of diverse species. This study aims to record and analyze the diversity of ant species in the area of Gunung Selindung of Twi Mentibar Village in Selakau Sub-District of Sambas Regency. The research method was purposive sampling where the placement of traps was done intentionally according to the presence of ants in three forest cover areas that is in open, medium and closed fores areas, divided into two area namely terestrial strata and arboreal. The results showed that there where nine species of ants (Formicidae) found in the Mount Selindung Forest area, namely black field ants (Formica sp), rang-rang (Oecophyllasp) pudak ant (Tapinoma melanocep), the black garden ant (Lasius niger), black ant (Dolichoderus teracicus), yellow crazy ant (Anoplolepis gracilipes), jumping ant (Harpagenethas Saltator), honey ant (Myrmecocystus sp), andÂ sembadak ant (Odontomachus sp). The diversity index of the terestrial (H '), of three types of forest cover areas, namely closed areas (H' = 0.63), moderate (H '= 0.76), and open area strata(H '= 0.73), all still showes the value of low species diversity; the species diversity index int the arboreal (H '), of the three types of forest cover areas namely closed area (H '), moderate (H = 0.61), and open area (H '= 0.55) all still showes the value of low species diversity. keyword: Ants, protected fores, , species diversity, Twi Mentibar Village